New treatment options for iron deficiency in women of different ages - Yu.E. Dobrokhotova; E.A. Markova (LCC «Medicine-Inform», 2022)
Yu.E. Dobrokhotova, E.A. Markova Pirogov Russian National Research Medical University, Moscow, Russian Federation Nowadays, iron-deficiency anemia (IDA) in pregnant and perimenopausal women has become an important social and healthcare problem. Despite the implementation of various projects and the availability of multiple clinical guidelines on early anemia diagnosis and prevention, no significant reduction in the global prevalence of IDA is observed. The article discusses the clinical efficacy of a new combination drug, containing ferrous sulfate and folic acid which is used for the treatment of iron deficiency during pregnancy, and the assessment of ferrous sulfate efficacy in perimenopausal women. The article presents a review of literature sources published in the last five years which describe the trials of sustained-release bivalent iron formulations with and without folic acid. The drugs were administered to women with gynecologic diseases that caused a chronic iron loss during menopause and to patients with iron deficiency during pregnancy. The authors discuss the most i mportant findings of the clinical trials assessing sustained-release bivalent iron formulation and its combination with folic acid which were used for treating pregnant women and gynecological patients of different ages. The literature data demonstrate that the combination drug, containing ferrous sulfate and folic acid is characterized by high clinical efficacy in the studied female populations with IDA. Keywords: sideropenia, iron deficiency, iron-deficiency anemia, pregnancy, bivalent iron, folic acid, menopause, perimenopause, gynecological diseases. For citation: Dobrokhotova Yu.E., Markova E.A. New treatment options for iron deficiency in women of different ages. Russian Journal of Woman and Child Health. 2022;5(3):201-208 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-201-208.